'Do you need a kayak to learn outside?': a literature review into learning outside the classroom. Issue 3 (3rd April 2019) - Hawxwell, L.; O'Shaughnessy, M.; Russell, C.; Shortt, D.
ABSTRACT: This paper presents a review of research focusing on 'Learning Outside the Classroom' (LOtC). We provide a distillation of international research in this field that identifies how future investigations could be focused and move the discipline forward. As a consequence of the breadth of our study, we feel our findings will have applications in educational settings across the globe. What we discover is a significant bias towards types of learning that largely cannot be measured, and that only a minority of published research in our review pays the level of attention to theoretical and philosophical foundations found in most other educational research.